If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4Y + -3Z = 4 Solving 4Y + -3Z = 4 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '3Z' to each side of the equation. 4Y + -3Z + 3Z = 4 + 3Z Combine like terms: -3Z + 3Z = 0 4Y + 0 = 4 + 3Z 4Y = 4 + 3Z Divide each side by '4'. Y = 1 + 0.75Z Simplifying Y = 1 + 0.75Z
| 4x-6=9x-10 | | 75-x=159 | | 5X-2Y+X=0 | | (2u-5)(8-u)=0 | | 5(7x+3y)-4(8x^2-7y^2)= | | 2.6x-86=1.5x+2 | | x-12.50+0.1x=0.2 | | 9.8=5x+8.5 | | 6.5x+8-3.5x=5 | | -4y+7=27 | | y^4+2x^2-4xy=-2 | | -5(9a+6)= | | 0.5x+0.1=1.9 | | 2x+15=15x+13 | | 2(x-7.1)=9.4 | | -5=-5+d | | 6x+8.57=3x+14 | | a+18=75 | | 31.82-2y=-4.5+3.92 | | x^2-5x-14=17 | | -9b^2+8b-8=0 | | 3x1/3= | | 4ln(3x-5)3=18 | | -20x+29=20x+29 | | (x-7)(x+2)=17 | | 19x+16=86 | | p-13=31 | | a(x)+b=c | | 7e-4(6+2w)=3(w-8) | | -4(5x-7)+1=20x+29 | | 25x+20=78 | | 47x=46x+1 |